Reduced Contraction of Blood Clots in Venous Thromboembolism Is a Potential Thrombogenic and Embologenic Mechanism - Peshkova, Alina D.; Malyasyov, Dmitry V.; Bredikhin, Roman A.; Le Minh, Giang; Andrianova, Izabella A.; Tutwiler, Valerie; Nagaswami, Chandrasekaran; Weisel, John W.; Litvinov, Rustem I. (TH Open, 2018)
Contraction (retraction) of the blood clot is a part of the clotting process driven by activated platelets attached to fibrin that can potentially modulate the obstructiveness and integrity of thrombi. The aim of this work was to reveal the pathogenic importance of contraction of clots and thrombi in venous thromboembolism (VTE). We investigated the kinetics of clot contraction in the blood of 55 patients with VTE. In addition, we studied the ultrastructure of ex vivo venous thrombi as well as the morphology and functionality of isolated platelets. Thrombi from VTE patients contained compressed polyhedral erythrocytes, a marker for clot contraction in vivo. The extent and rate of contraction were reduced by twofold in clots from the blood of VTE patients compared with healthy controls. The contraction of clots from the blood of patients with pulmonary embolism was significantly impaired compared with that of those with isolated venous thrombosis, suggesting that less compacted thrombi are prone to embolization. The reduced ability of clots to contract correlated with continuous platelet activation followed by their partial refractoriness. Morphologically, 75% of platelets from VTE patients were spontaneously activated (with filopodia) compared with only 21% from healthy controls. At the same time, platelets from VTE patients showed a 1.4-fold reduction in activation markers expressed in response to chemical activation when compared with healthy individuals. The results obtained suggest that the impaired contraction of thrombi is an underappreciated pathogenic mechanism in VTE that may regulate the obstructiveness and embologenicity of venous thrombi.
Keywords: blood clotting; thrombosis; clot contraction; clot retraction; venous thromboembolism